Infection with Toxoplasma gondii increases the risk of psychiatric disorders in Taiwan: a nationwide population-based cohort study. Issue 13 (30th November 2020) - Lin, Hsin-An; Chien, Wu-Chien; Huang, Kuo-Yang; Chung, Chi-Hsiang; Chen, Lih-Chyang; Lin, Hsin-Chung; Guo, Jong-Long
Abstract: This study aimed to evaluate associations between toxoplasmosis and psychiatric disorders in Taiwan based on the National Health Insurance Research Database, Taiwan (1997–2013). Patients newly diagnosed with toxoplasmosis formed the case group ( n = 259), and the control group included propensity-score matched patients without toxoplasmosis ( n = 1036). The primary outcome was incidence of psychiatric disorders. Cox proportional hazards regression and stratified analyses were performed to examine risk of developing specific psychiatric disorders between patients with and without toxoplasmosis. Patients with toxoplasmosis had significantly higher incidence of psychiatric disorders than those without toxoplasmosis ( P = 0.016). A significant difference was found in numbers of psychiatric disorders between the two groups during 14 years of follow-up (log-rank P < 0.001). Those with toxoplasmosis had significantly higher risk of bipolar disorder [adjusted hazard ratio (aHR = 3.60, 95% confidence interval (CI) = 2.07, 7.26), depression (aHR = 4.94, 95% CI = 2.15, 11.80) and anxiety (aHR = 5.36, 95% CI = 2.98, 25.88), but no significant between-group differences were found for schizophrenia and other psychiatric disorders. In conclusion, the present nationwide population-based analysis revealed that Toxoplasma gondii infection in Taiwan significantly increases the risk for developing bipolar disorder, depression and anxiety, but not for schizophrenia and other psychiatric disorders.